Digital comics in primary education: A literature review on reading literacy and local wisdom integration (2020–2025) - Kadek Sintya Pratiwi; Agung Tri Prasetya; Arif Widiyatmoko; Bambang Subali (Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2025)
Reading literacy skills are a fundamental competency for elementary school students. However, various surveys indicate that the level of reading literacy in Indonesia remains low. This situation underscores the need for innovative learning media that are engaging, contextual, and aligned with the characteristics of the digital generation. This study aims to investigate trends in the use of digital comics in primary education—particularly for improving reading literacy and integrating local wisdom—during the 2020–2025 period. The study employs a Systematic Literature Review (SLR) guided by PRISMA methodology, encompassing the stages of identification, screening, eligibility, and inclusion. Data were gathered from Google Scholar, Semantic Scholar, and Crossref. From an initial 3,358 articles, a final selection of 27 relevant articles was obtained. Analysis was conducted via content analysis and bibliometric techniques using VOSviewer 1.6.19. The results show a significant increase in publications on e-comics from 2020 to 2023. Digital comics were found to be effective in enhancing students’ reading comprehension, motivation, and character development through the integration of local cultural values. They also have the potential to serve as an innovative and contextually relevant, culture-based multimodal learning medium.